Análise dos serviços ofertados de telecomunicações no Brasil: período pós-privatização - Benelli, Alexandre Liria (2017)
This bibliographical research shows a study about the changes in the telecommunications sector after it’s privatization in Brazil. It describes the historic before and after the privatization of this sector in Brazil, the types of services offered, mergers between companies that occurred, a description of regulated services and unregulated telecommunications substitutes services and their influence on the sector, with historic data of increase of using by cable TV, traditional and mobile telephone lines in Brazil and a Porter analysis about the actual telecommunication market.